ANALISIS PENGARUH PENAMBAHAN ELEKTRODA TERHADAP NILAI TAHANAN PENTANAHAN TOWER 105 SUTT 150KV MANINJAU - PADANG LUAR - Randi Gunawan; Yulisman Yulisman; Mahyessie Kamil (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In the process of distributing electrical energy, the transmission system plays an important role, for the conductor of the 150 kV High Voltage Air Line (SUTT) that connects the GI. Review with GI. The Padang Luar grounding system plays a very important role in reducing the impact of disturbances caused by lightning. For this reason, security is needed that can secure this SUTT from various disturbances that occur along its path. The value of the stability of this grounding system must be maintained in accordance with predetermined standards in order to maintain the quality of the distribution, especially when there is potential for interference from the transmission line.The standard for the grounding value that must be used is that it must be below 10 . Evaluation of the value of grounding resistance in the conductor is carried out to maintain, maintain and or improve the quality of the grounding because the value of grounding resistance can change from time to time due to the influence of the resistance value of the soil type and the grounding system itself.Tower 105 which has a grounding resistance value above 10 , it is necessary to reduce the ground resistance value, based on the calculations carried out, more effective results are obtained by using a grounding system of two electrode rods planted perpendicular to the ground for S > L, using an electrode with a diameter of 1 “(25.40 mm) can reduce the value of grounding resistance at the foot of the tower (stub. A) by 37.72% from 12.46 W to 7.76 W; tower foot (stub. B) by 37.71 % from 12.65 W to 7.88 W; tower foot (stub. C) by 37.70% from 13.37 W to 8.33 W; and the tower legs (stub. D) amounted to 37.74% from 14.31 W becomes 8.91 W. Keywords: transmission, soil resistivity, electrode grounding resistance